“Rediseño y acondicionamiento del sistema eléctrico del bloque B en la Universidad técnica de cotopaxi extensión La Maná”. - Veloz Guerra, Kaina Micaela (2022)
In the project, the study and reconditioning of the low-voltage electrical distribution system of the facilities in the block B of the Technical University of Cotopaxi La Maná Extension was carried out. In the infrastructure, there is evidence of a deterioration in terms of the state of its electrical distribution systems, both in its physical components such as boards and conductors. In the same way, the lack of maintenance and performance records of these showed the need to carry out an electrical and measured study of its system that demonstrates the status of the quality and reliability of the supply. With these precedents, we proceeded to detail the electrical components present in the installation, their rooms and layout, with which the electrical plans for elimination and strength were updated. In terms of the main feeders and the main and secondary distribution boards, they were changed and reconditioned applying the Ecuadorian regulations for the construction of electrical installations. Likewise, an external conditioning was carried out on the power transformer and the labeling of electrical equipment according to single-line and multi-line diagrams of the installation, also carried out. Finally, measurements of important electrical parameters such as voltage, current and frequency were taken at strategic points of the installation to identify problems and solutions in the system, which are shown in the results. A significant improvement was obtained in the distribution of electrical components and in the values of the electrical measurements in the strategic points.